2008
DOI: 10.1128/iai.01481-07
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Are Mediators of Gastritis in Acute Helicobacter pylori Infection in C57BL/6 Mice

Abstract: Helicobacter pylori is the etiological agent of human chronic gastritis, a condition seen as a precursor to the development of gastrointestinal ulcers or gastric cancer. This study utilized the murine model of chronic H. pylori infection to characterize the role of macrophages in the induction of specific immune responses and gastritis and in the control of the bacterial burden following H. pylori infection and vaccination. Drug-loaded liposomes were injected intravenously to deplete macrophages from C57BL/6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 26 publications
2
73
0
Order By: Relevance
“…One hypothesis for the mechanism of H. pylori-induced pathology is that during persistent infection an unresolved inflammatory response, possibly involving macrophages, contributes to severity of disease. Depletion of macrophages in vivo has been suggested to confer protection against gastritis in the presence of high bacterial loads (65). We previously reported that miR-155 was up-regulated in gastric biopsies of human volunteers infected with H. pylori for 80 d, and a major infiltration of macrophages/DCs was detected at the RNA level (15).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis for the mechanism of H. pylori-induced pathology is that during persistent infection an unresolved inflammatory response, possibly involving macrophages, contributes to severity of disease. Depletion of macrophages in vivo has been suggested to confer protection against gastritis in the presence of high bacterial loads (65). We previously reported that miR-155 was up-regulated in gastric biopsies of human volunteers infected with H. pylori for 80 d, and a major infiltration of macrophages/DCs was detected at the RNA level (15).…”
Section: Discussionmentioning
confidence: 99%
“…As macrophages are known to have a critical role in H. pylori-mediated gastritis (14,37) and C. rodentium colitis (14), we sought to interrogate the specific role of ODC in macrophages during these enteric infections, using a myeloid/macrophage-specific Odc knockout mouse.…”
Section: Significancementioning
confidence: 99%
“…Pathology and gastritis were graded as previously described [28,55]. Briefly, the severity of chronic inflammation was assessed and graded according to the density and distribution of lymphocytes.…”
Section: Gastritis Scoringmentioning
confidence: 99%